2022
DOI: 10.1177/21582440221095021
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Support in Article Publication: Perspectives of Non-Native English Speaking Doctoral Students in a “Publish or No Degree” Context

Abstract: Article publication as a requirement for graduation appears to be the most compelling challenge for doctoral candidates, especially for the non-English speaking ones. In order to contribute to this topic of growing interest, we aimed to investigate the key challenges to doctoral student research publication and develop an understanding of support they needed to ease the publication process. To this end, we conducted semi-structured interviews with 19 non-English speaking doctoral students in varied science and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, recent reports are already showing glimpses of this happening. Some doctoral programs have already imposed a "publish or no degree" policy (Shamsi & Osam, 2022), which withholds doctoral student graduation unless a publishing ransom is paid. Under such pressures, we fear that students may resolve to predatory journals as potential avenues, cut corners in rigor when executing their research, and/or worst still, turn to unethical research practices, such as neglecting ethical human research conduct, unprincipled data manipulation, and plagiarism to accelerate outcomes (e.g., Dolnicar, 2019).…”
Section: Publish or Perish: Origins And Influence On Tourism Academiamentioning
confidence: 99%
“…Unfortunately, recent reports are already showing glimpses of this happening. Some doctoral programs have already imposed a "publish or no degree" policy (Shamsi & Osam, 2022), which withholds doctoral student graduation unless a publishing ransom is paid. Under such pressures, we fear that students may resolve to predatory journals as potential avenues, cut corners in rigor when executing their research, and/or worst still, turn to unethical research practices, such as neglecting ethical human research conduct, unprincipled data manipulation, and plagiarism to accelerate outcomes (e.g., Dolnicar, 2019).…”
Section: Publish or Perish: Origins And Influence On Tourism Academiamentioning
confidence: 99%
“…The first examines the structure of discussion sections in research articles by Indonesian writers (Arsyad et al, 2020;Hilmi & Afifi, 2021;Arsyad et al, 2021). The second angle explores the challenges students face in writing articles (Lesmana & Ariffin, 2020;Shamsi & Osam, 2022;Purwanto, 2021). The third focuses on discourse studies, analyzing linguistic features in articles by nonnative English speakers published in Englishmedium journals (Martinez, 2018;Alipour & Nooreddinmoosa, 2018;Lathif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These studies draw on such social constructivist theories as academic literacies and situated learning as theoretical frameworks to analyse EAL scholars' challenges, coping strategies and learning in writing and getting published (Flowerdew & Habibie, 2022). Language problems in the writing process (grammatical mistakes, poor vocabulary, lack of conciseness, informal language etc.,; Abdeljaoued & Labassi, 2020; Lei & Hu, 2019; Luo & Hyland, 2019; Mu, 2020; Mur‐Dueñas, 2013; Ramirez‐Castaneda, 2020; Shamsi & Osam, 2022; Uzuner, 2008; Willey & Tanimoto, 2012) and in submission (understanding the rules of the journal, completing the submission procedures, communicating with editors and reviewers etc. ; Mu, 2020; Yuan et al, 2020) were reported most frequently among the challenges.…”
Section: Introductionmentioning
confidence: 99%